Pengaruh Muatan Etika dalam Pendidikan Akuntansi terhadap Persepsi Etika Mahasiswa (Studi pada Mahasiswa Jurusan Akuntansi Universitas Brawijaya Malang Angkatan 2009) - Lita Permata Sari; Ari Kamayanti (Jurnal Ilmiah Mahasiswa FEB, 2012)
This aim of this research is to reveal the influence of the effect of the charge of ethics in accounting education as the duty of spiritual inner reflection, ethical issue, discussion, and resolution of ethical case against ethical perceptions of students. The population of the research is undergraduate students of the Department of Accounting, Faculty of Economics and Business, Brawijaya University, year 2009 currently undergoing an auditing practice and has taken courses in business ethics and professions. The data of this research is taken by using questionnaire as primary data. There were 167 questionnaires given out but only 135 questionnaires which meet the criteria of sampling. This research uses mixed method, as a combination of qualitative and quantitative research methods. To analyze variables, this research uses simple regression analysis. The result shows that the charge of ethics in accounting education has significant influence on  student’s ethics perceptions with 5% significance tolerance. Keywords: Keywords: Charge ethics, ethical perception